Identification of a Microdeletion at the 7q33-q35 Disrupting the CNTNAP2 Gene in a Brazilian Stuttering Case - Petrin, Aline L.; Giacheti, Célia Maria [UNESP]; Maximino, Luciana P.; Abramides, Dagma Venturini Marques; Zanchetta, Sthella; Rossi, Natalia F. [UNESP]; Richieri-Costa, Antonio; Murray, Jeffrey C. (Wiley-liss, 2010)
Speech and language disorders are some of the most common referral reasons to child development centers accounting for approximately 40% of cases. Stuttering is a disorder in which involuntary repetition, prolongation, or cessation of the sound precludes the flow of speech. About 5% of individuals in the general population have a stuttering problem, and about 80% of the affected children recover naturally. The causal factors of stuttering remain uncertain in most cases; studies suggest that genetic factors are responsible for 70% of the variance in liability for stuttering, whereas the remaining 30% is due to environmental effects supporting a complex cause of the disorder. The use of high-resolution genome wide array comparative genomic hybridization has proven to be a powerful strategy to narrow down candidate regions for complex disorders. We report on a case with a complex set of speech and language difficulties including stuttering who presented with a 10Mb deletion of chromosome region 7q33-35 causing the deletion of several genes and the disruption of CNTNAP2 by deleting the first three exons of the gene. CNTNAP2 is known to be involved in the cause of language and speech disorders and autism spectrum disorder and is in the same pathway as FOXP2, another important language gene, which makes it a candidate gene for causal studies speech and language disorders such as stuttering. (C) 2010 Wiley-Liss, Inc.
Keywords: microdeletion; CNTNAP2; stuttering